Relationship between motivation and organizational commitment among scout volunteers in East Kalimantan - Rahmawati, Yeni; Zainal Abiddin, Norhasni; Ro'is, Ihsan (Macrothink Institute, 2015)
Numerous studies have been concerned on organizational commitment among profit worker oppositely organizational commitment’s studies which focused on nonprofit worker tend to be lack. Nonprofit employee generally recruit and involve volunteer to run their program. Several nonprofit organizations’ program is related to non-formal education. For that matter, this study was conducted to evaluate volunteer involvement which especially concern on non-formal education. The objective of this study is to examine relationship between motivation and organizational commitment among volunteer scout as well as find the best predictor affecting organizational commitment. This study used volunteer scout organization since this organization run within non-formal education area. The research used quantitative study to analyze the data. The instrument that has been utilized to collect the data was self administered questionnaire. The data was analyzed descriptively as well as inferentially. The questionnaire was divided into several parts: demographic, Volunteer Function Inventory (VFI), and Organizational commitment (OCQ). The data collection was taken in Samarinda city which located in East Kalimantan-Indonesia. The questionnaire was administered to 207 participants from scout movement center organization. The sample was taken by using random sampling technique and using Scout volunteer in Scout Center-Samarinda as the subject. Finally, the finding of the study revealed that overall motivation as well as the dimension was positively correlated to organizational commitment. Meanwhile, understanding dimension was considered become the best predictor affecting organizational commitment among volunteer scout in East Kalimantan, Indonesia. Several implications were emerged from non-formal education view as well as nonprofit area.